Pengaruh Perceived Ease Of Use, Fianancial Literacy Terhadap Keputusan Belanja Online Shoping dengan Islamic Lifestyle sebagai Faktor Pemoderasi - Khairani, Zelfia; Rusyaida, Rusyaida (Jurnal Ilmiah Global Education, 2025)
The growth of information technology is growing rapidly in Indonesia, including in the city of Bukittinggi, West Sumatra province. So that it changes the tendency of millennial lifestyles towards using gadgets with the ease of features and applications offered. One of them is the widespread use of online shopping among millennials due to the ease of buying products with technological advances. The focus of this study is to see the use of online shopping among millennials. The purpose of this study is to see the effect of perceived ease of use and financial literacy on the decision to use online shopping with Islamic lifestyle as a moderating factor. This study uses primary data using the quantitative correlation research method with a Likert scale instrument distributed through Google Form as many as 150 samples using purposive sampling, which is a non-probability sampling technique. The data analysis tool in this study uses Warp PLS 8.0. The results of this study show that perceived ease of use and financial literacy have a significant effect on online shopping decisions, while Islamic lifestyle has a positive effect as a moderating factor between perceived ease of use and financial literacy on online shopping decisions